Congenital Unilateral Posteromedial Bowing of Tibia in an Adolescent: A Rare Presentation of Tibial Bowing - Nikhil Jain; Nibin Sunny; Pranjal Mishra (Journal of Orthopedics, Traumatology and Rehabilitation)
Posteromedial bowing of the tibia is a relatively uncommon congenital anomaly. Etiology is not fully understood. Usually, the deformity improves with time and most of the cases are managed conservatively with modifications in shoes. In case of any residual deformity or significant limb length discrepancy, there is a need of surgical procedures either to retard the growth of the normal limb by epiphysiodesis or lengthening of the affected limb using the principles of distraction osteogenesis. Here, we are reporting a rare presentation of posteromedial bowing of the tibia in the unilateral leg managed by conservative measures.